Iatrogenic Peroneal Nerve Palsy Rates Secondary to Open Reduction Internal Fixation for Tibial Plateau Fractures Using an Intraoperative Distractor. Issue 7 (July 2020) - Pattyn, Ryan; Loder, Randall; Mullis, Brian H.
Abstract : Objective: To report the rate of peroneal nerve palsy after routine use of intraoperative distraction during open reduction internal fixation (ORIF) for lateral unicondylar and bicondylar tibial plateau fracture (TPF) repairs. Design: Retrospective chart review. Setting: Level I trauma center. Patients: Patients with traumatic TPF treated with ORIF between 2007 and 2017. Intervention: ORIF for lateral unicondylar and bicondylar TPF. Main Outcome Measurement: Presence and resolution of neurovascular injury. Results: There were a total of 21 lateral unicondylar and 40 bicondylar TPFs repaired through ORIF in 60 patients identified during the study period with 1-year follow-up and complete records for review. Thirty-six patients had staged external fixation before ORIF while 24 were treated with ORIF initially. Of the staged patients, 9 of 36 (25%) developed nerve palsy while those undergoing initial ORIF (not staged) developed palsy in only one case (1 of 24, or 4%). Of the patients who developed nerve palsy, 9 of 10 (90%) were staged with an initial external fixator before ORIF. The incidence of iatrogenic peroneal nerve palsy secondary to intraoperative distraction was 16.4% (10 of 61). Only 60% (6 of 10) of peroneal nerve palsies recovered clinically with a mean recovery time of approximately 14 weeks. Comparison of demographics in patients with peroneal nerve palsy versus those without yielded no significant difference by sex ( P = 0.08), age ( P = 0.27), fracture type ( P = 0.29), tobacco use ( P = 0.44), or alcohol use ( P = 0.78). Conclusions: Peroneal nerve palsy is a common sequela of ORIF for TPFs involving the lateral compartment using an intraoperative distractor. Staged external fixation followed by definitive ORIF using intraoperative distraction was associated with significant risk for developing nerve palsy (9/10). Many patients (40%) who develop peroneal nerve palsies do not recover, leading to permanent loss of motor and/or sensory function for 7% of patients studied. None of the epidemiologic variables evaluated yielded predictive value for development of peroneal nerve palsy or subsequent resolution. Caution should be exercised in avoiding overdistraction when using intraoperative distraction, especially in those cases that had staged fixation, most notably bicondylar injuries. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.